Transforming the School Literacy Movement (GLS): Teachers' Strategies to Integrate the Digital-Based Reading Literacy Ecosystem in Elementary Schools - Wasilurrahman; Mohammad Ali Fahmi Ramadhana; Yanti Linarsih (Molang: Journal Islamic Education, 2026)
The School Literacy Movement (GLS) at the elementary school level is often still stuck in the mechanical routine of reading printed books for 15 minutes before lessons start, without meaningful pedagogical integration. In today's era of digital disruption, the cognitive and behavioral characteristics of elementary school students, who are inherently digital natives, demand the adaptation of learning media that is much more interactive, multimodal, and ecosystemically connected. This study aims to comprehensively review the literature related to teachers' innovative strategies in transforming conventional GLS into a digital-based reading literacy ecosystem, as well as identifying the various structural and cultural challenges that accompany it. This study uses a qualitative approach with the Systematic Literature Review (SLR) method through the extraction of empirical data from various academic publications. Key findings show that the most effective teacher strategies focus on the integration of information technology (IT)-based learning media that is balanced with Technological Pedagogical Content Knowledge (TPACK) competencies. The paradigm shift in the role of teachers from mere supervisors of reading activities to curators and facilitators of digital literacy has been empirically proven to be able to increase students' active participation, deepen reading comprehension through visual-auditory stimulation, and build critical reasoning skills. The conclusion of this study emphasizes that the transformation of GLS is not just a process of digitizing texts, but a re-engineering of the pedagogical ecosystem that requires the adaptive capacity of teachers and synergistic collaboration from all stakeholders to create a sustainable literacy culture.